Ekplorasi Rhizobakteri Dengan Kemampuan Menghasilkan Metabolit Anti Nematoda Terhadap Meloidogyne spp - Dinasty Azzahra (Fakultas Pertanian, 2025)
The purpose of this study was to determine safe and effective isolates that are able to produce secondary metabolites to control Meloidogyne spp. nematodes in vitro. The study was conducted from October to December 2024 at the Plant Pest Laboratory, Faculty of Agriculture, University of Jember. Rhizosphere samples were taken from organic chili fields in Arjasa District, Jember Regency. The rhizosphere sampling technique was carried out using the random sampling method. The rhizosphere results were subjected to several characterizations and tests of Meloidogyne spp. in vitro. The isolation results obtained 20 isolates by knowing the colony morphology macroscopically and microscopically. The results of the HR reaction test found 10 isolates which were continued with testing against Meloidogyne spp. in vitro. The results of testing against Meloidogyne spp. showed that 10 isolates had significantly different values from the control. The results of the antagonist test showed that 10 isolates were effective in inhibiting egg hatching and mortality of J2 Meloidogyne spp. in vitro. The highest hatching inhibition value was obtained in isolate DA18 and the highest value obtained in the mortality results of Juvenile 2 Meloidogyne spp. namely DA17 and DA12. Based on the results of the proteolytic activity test of the three isolates, it was obtained that DA17 and DA18 had proteolytic activity and phosphate solubilizing activity, while DA12 did not have proteolytic activity and phosphate solubilizing activity.
Reaploud Repository February_Hasyim
Keywords: Rhizosphere; Isolates; Meloidogyne Spp.; In Vitro.